أثر الضرورة الشعرية في تطور البنى الصرفية الاسمية وضرورة التغيير / The effects of Poetical necessities in developing the nominal morphological structures: the essential poetical changes - Ḥusein Muqablah, Alaa (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: يتناول هذا البحث تأثير الضّرورات الشّعريّة في إثراء اللغة وتنمية صيغها الصرفية؛ فلم يُكْتفَ بدراسة الضّرائر في مصادرها، وإنّما اقتضت الدراسة أن يعرض ما في كتب الضرورة على أربعة معاجم توزعت على حقب زمنية مختلفة ابتداء من القرن الرابع وانتهاء بالقرن الثالث عشر؛ الأمر الذي يتيح رصد التطور بوضوح. وقد اعتنى البحث على وجه الخصوص بتلك الصيغ الصرفية التي تعرضت لتغيير الوزن أو التّغيير بالإبدال والإعلال، وقسّم ألفاظ نوعي التّغيير السابقين إلى أقسام هي الجموع، وأسماء الجنس، والمصادر، والمشتقات. وقد خلص البحث إلى أنّ عدداً من الضّرورات الشّعريّة غدت جزءاً من اللغة المستعملة، وصارت مما تواضع أصحاب المعاجم على أنّه جزء من اللغة السائغ استعماله بلا محاذير، وكذلك خلص البحث إلى أنّ التّغيير في الجموع حظي بنصيب الأسد، فمن أصل سبع عشرة حالة تعرض لها البحث جاء التّغيير في الجموع في عشرة مواطن، وقد كان سبعة منها من صيغة منتهى الجموع؛ أما المصادر فحظيت بـأربع حالات، وورد التّغيير في المشتقات في موطنين، في حين لم يحظ اسم الجنس إلا بحالة واحدة. الكلمات المفتاحيّة: الضّرورة الشّعريّة، البنى الصّرفيّة، البنى الاسميّة، تطوّر الأبنية. Abstract The study discusses the effects of Arabic poetical necessities which are the strategies to preserve the poetical meters through what is normally forbidden in the prose; in terms of their effects in enriching the language and enhancing its morphological structures. The study is not constrained in studying the strategies in their sources but to discuss also such strategies in four dictionaries compiled in different period of time beginning from the fourth century until the thirteenth century that would clarify the issue at hand in a clearer manner. The study would specifically focus on the changed morphological structures through the processes of ‘ibdal’ (change of letter) and ‘I’lal’ (change of vowel). The words for both of these two processes will be divided into several categories such as: plural, nouns of types, verbal nouns and derivative nouns. The study concluded that some of the poetical necessities are part of the used language that are endorsed by lexicographers and are widely used and accepted. The study concluded that the plural form is the most affected. Ten forms of change in the plural nouns were detected in the seventeen structures of plural, seven of them are of the structure of ‘muntaha jama’, as for verbal nouns, four structures were affected, the derivative nouns were affected in two structures, and the noun type was not affected except in one situation. Keywords: Poetical necessities, morphological structures, noun structures, development of structures. Abstrak Kajian ini membicarakan tentang kesan-kesan dharurat syair (strategi-strategi untuk mengekal wazan syair melalui cara yang biasanya adalah dilarang di dalam prosa) dalam mengembang dan memperkaya kosa kata dan struktur wazan dalam Saraf bahasa Arab. Kajian ini turut mengkaji empat kamus-kamus yang disusun dalam tempoh masa berbeza seawal kurun keempat sehinggalah kurun ke tiga belas untuk menegaskan persoalan ini dengan lebih jelas. Kajian ini akan menumpukan kepada perubahan struktur yang diakibatkan oleh proses ibdal (perubahan konsonan) dan I’lal (perubahan vowel). Perkataan-perkataan yang tehasil daripada kedua-dua proses ini akan dibahagikan kepada beberapa kategori seperti kata majmuk, kata nama jenis, kata nama perbuatan dan kata nama terbitan. Kajian ini merumuskan bahawa ada sebahagian dharurat puisi ini telah menjadi sebahagian daripada bahasa yang diguna pakai yang turut dimuatkan oleh para penyusun kamus dalam karangan mereka. Kajian in mendapati struktur bentuk kata majmuk paling banyak terkesan. Sepuluh bentuk perubahan struktur dalam kata nama telah dikesan dalam kalangan tujuh belas struktur kata majmuk; tujuh daripadanya adalah daripada struktur ‘muntaha jamak’. Untuk kata nama perbuatan, empat struktur telah mendapat kesan, kata nama terbitan terkesan dalam dua strukturnya. Manakala jenis kata nama jenis tidak mendapat kesan kecuali dalam hanya satu keadaan sahaja. Kata kunci: Dharurat Syair, struktur saraf, struktur-struktur kata nama, perubahan struktur.